Animals should definitely not act like people - Barrett, Judi (New York : Aladdin Paperbacks, 1980)
Depicts the inconveniences animals would be burdened with if they behaved like people.
Keywords: Animals -- Juvenile humor; Animal behavior -- pictorial works; American wit and humor